2015
DOI: 10.1038/srep11315
|View full text |Cite|
|
Sign up to set email alerts
|

Electroporation enables the efficient mRNA delivery into the mouse zygotes and facilitates CRISPR/Cas9-based genome editing

Abstract: Recent use of the CRISPR/Cas9 system has dramatically reduced the time required to produce mutant mice, but the involvement of a time-consuming microinjection step still hampers its application for high-throughput genetic analysis. Here we developed a simple, highly efficient, and large-scale genome editing method, in which the RNAs for the CRISPR/Cas9 system are electroporated into zygotes rather than microinjected. We used this method to perform single-stranded oligodeoxynucleotide (ssODN)-mediated knock-in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
231
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(235 citation statements)
references
References 10 publications
(13 reference statements)
4
231
0
Order By: Relevance
“…In addition, recent reports showed that gene-edited mice can be generated by direct injection of Cas9 protein, instead of Cas9 mRNA [29,30]. Furthermore, electroporation enables efficient mRNA delivery into mouse and rat zygotes [31,32]. Although microinjection into zygotes requires specialized skills and is difficult for beginners to perform, electroporation is simple and easy for beginners to perform.…”
Section: Genome Editing In Micementioning
confidence: 99%
“…In addition, recent reports showed that gene-edited mice can be generated by direct injection of Cas9 protein, instead of Cas9 mRNA [29,30]. Furthermore, electroporation enables efficient mRNA delivery into mouse and rat zygotes [31,32]. Although microinjection into zygotes requires specialized skills and is difficult for beginners to perform, electroporation is simple and easy for beginners to perform.…”
Section: Genome Editing In Micementioning
confidence: 99%
“…11 These efforts have overcome the aforementioned shortcomings with improved intracellular stability and translational efficiency. 22,23 Nowadays, IVT mRNA has undergone extensive clinical or pre-clinical investigation in the elds of therapeutic cancer vaccination, 24-27 cell programming [28][29][30] and so on, demonstrating great potential.…”
Section: -14mentioning
confidence: 99%
“…A second round of confirmatory experiments, performed on a gene-by-gene approach, could confirm the gene identification process. The rate-limiting step for such a CRISPR-based genetic screening in mice is oocyte microinjection, which could be replaced by oocyte electroporation (Hashimoto & Takemoto 2015, Qin et al 2015, Takahashi et al 2015.…”
Section: Crispr/cas9 and The Future Of Endocrinologymentioning
confidence: 99%